PREVENTION OF NON-COMMUNICABLE DISEASES (NCDs) THROUGH EXAMINATION, EARLY DETECTION AND INCREASING KNOWLEDGE - Agustin, Ismar; Azwaldi, Azwaldi; Muliyadi, Muliyadi; Putri, Prahardian (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Indonesia is facing a double burden of disease where infectious diseases are still a problem and at the same time non-communicable diseases (NCDs) are increasing, causing the burden on society and the state to become increasingly heavy socially and economically. Efforts to improve people's quality of life still receive little attention. The Healthy Society Movement (GERMAS) through efforts to detect non-communicable diseases (PTM) needs to continue to be strengthened. GERMAS is a joint movement which is not only the responsibility of the government through the health service but is also the responsibility of the community, including academics. Several obstacles to the implementation of germas include limited access and not yet optimal community participation. Purpose of Community Service. increasing the achievement of Early Detection of NCDs for the community in the working area of ​​the Sako Palembang Community Health Center in 2023. The solution to the problem is carried out through screening and Early Detection as well as increasing understanding of NCDs in the community through counseling and personal education in the working area of ​​the Sako Palembang Community Health Center in 2023. Activities are carried out through the preparatory stages , implementation and evaluation . The resulting output is in the form of increasing knowledge, understanding and behavior for the community in the work area of ​​the Sako Palembang Community Health Center in 2023, in addition to producing booklets/posters and community service publications.